2018
DOI: 10.1109/jstqe.2017.2771744
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spectral Filtering on Multipulsing Instability in Mode-Locked Fiber Lasers

Abstract: Abstract-We investigate the impact of spectral filtering in mode-locked fiber lasers with an extended geometrical model. Our iterative model, which includes gain, loss and the pulse shaping effects of chromatic dispersion and selfphase modulation, is used to model the laser cavity dynamics. Simulations show that broadband pulses experience large losses from spectral filtering in the cavity, leading to a number of potential laser instabilities and outcomes such as multi-pulsing, periodic and chaotic states, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In order for the modelocked pulse to be stable, it follows that a small perturbation away from the modelocked pulse must experiences net loss. This result is consistent with prior work on multiple pulse modelocking dynamics [29,[42][43][44][45][46]. Physically, the single channel modelocked pulse experiences the loss from the filter.…”
Section: Stability Of the Modelocked Statessupporting
confidence: 90%
“…In order for the modelocked pulse to be stable, it follows that a small perturbation away from the modelocked pulse must experiences net loss. This result is consistent with prior work on multiple pulse modelocking dynamics [29,[42][43][44][45][46]. Physically, the single channel modelocked pulse experiences the loss from the filter.…”
Section: Stability Of the Modelocked Statessupporting
confidence: 90%
“…It is known that spectral filtering plays a key role in the genesis and stability of dissipative solitons; where the spectral filter is used to cut off the field at the end of each roundtrip so as to compensate for the large dispersion-induced positive chirp acquired during the roundtrip [5,6,7]. In soliton-like formation, spectral filtering has a key role also [8,9]. However, this is to some extent forgotten by the fact that most proposals naturally fall where standard fibers present the required anomalous dispersion; i.e., above 1.3 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Since, as the influence of spectral filtering on mode-locked fiber lasers is well known through several studies [18,19], our purpose in the present study is to investigate the impact of the higher-order spectral filtering on the stationary solutions of the CSHE. In recent studies, the effect of spectral filtering in mode-locked fiber lasers with an extended geometrical model was presented [20]. It was demonstrated that the spectral filtering leads to strong nonlinear dynamics in a mode-locked fiber laser cavity, which can be used to understand the pulse dynamics in mode-locked soliton fiber lasers.…”
Section: Introductionmentioning
confidence: 99%